(untitled) (The Agriculturists, 2017)
The experiment was conducted to determine the effect of irrigations and sowing dates on growth and yield performance of wheat in the experimental field of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during the period of November 18, 2012 to March 30, 2013. The experiment was comprised of two factors, viz. factor A: two irrigations namely irrigation (I) and no irrigation i.e. control (I0), and factor B: three sowing dates such as S1: 1st sowing on 18 November, S2: 2nd sowing on 03 December and S3: 3rd sowing on 18 December. The experiment was laid out in a split plot design with three replications. Irrigation was assigned in the main plot, while sowing time was in the sub-plots. Data on grain yield and different yield contributing characters were taken after harvest. Results indicated that the highest grain yield was obtained with I (2.915 t ha-1) and S1 (2.983 t ha-1). The interaction of irrigation (I) and sowing on 18 November (S1) showed the maximum yield (3.387t ha-1), spike length (17.08 cm), 1000 grain weight (43.4 g), spikelets spike-1 (20.03) and grain spike-1 (65.58) of wheat. The Agriculturists 2016; 14(2) 77-85